Comparison of alpha/beta T cell depletion with posttransplant cyclophosphamide in haploidentical transplantation - Ozen, Mehmet; Gunduz, Mehmet; Aksoyoglu, Ilknur; Irfan, Ahmet; Ural, Ali Ugur (EXPERIMENTAL BIOMEDICAL RESEARCH, 2023)
Aim: To compare alpha/beta T-cell depletion with posttransplant Cyclophosphamide (PTCy) in haploidentical allogeneic transplantation in adult hematological patients, this is the first study. Method: In our study, we reported 36 haploidentical allogeneic stem cell transplants which were performed in our clinic. Results: Twenty-six of these haploidentical transplants received standard treatment and transplanted either with PTCy (n=21, 81%) or with alpha/beta T-cell depletion (n=5, 19%). Less CD34+ stem cells were administered in the T-cell depletion group. When the two groups were compared in terms of survival, no difference was found in relapse-free and overall survival in each group. Acute GVHD cases developed in the PTCy group mostly developed after CMV infection, whereas acute GVHD did not develop in the T-cell depletion group. In the PTCy group, 8 cases developed graft failure and relapse; 4 cases developed graft failure or relapse in the T-cell depletion group, and 2 of them developed graft failure or relapse following EBV infection and 1 of them following CMV infection. Conclusion: We have a small number of patients in the T cell depletion group. Due to our long follow-up period, we believe that our patients with T cell depletion can be compared with those who underwent PTCy, and similar survival results can be achieved in adult patients having hematologic malignancies.